Exploring innovation perceptions and practices among micro and small craft breweries: A three-country study. Issue 2 (19th June 2017) - Duarte Alonso, Abel; Bressan, Alessandro; Sakellarios, Nikolaos
Abstract : Purpose: The purpose of this study is to examine how micro and small craft brewery operators perceive and operationalise innovation. Moreover, in adopting the theory of innovation, the study addresses two under-researched areas, namely, innovation among micro and small firms and innovation in the context of the emerging craft brewing industry. Design/methodology/approach: The perspectives of 163 craft brewery operators located in Italy, Spain, and the UK were gathered through online questionnaires. In total, 24 face-to-face and telephone interviews with operators from the three nations complemented the data collection process. Thus, in total, 187 operators participated. Findings: Development of new craft beer styles, new recipes, exploring with various ingredients, improving quality, or involvement in social media and culinary tourism were predominant forms participants perceived innovation. Various differences regarding innovation adoption were noticed, particularly based on participants' country and on their role at the brewery. Furthermore, associations between the findings and the dimensions of the theory of innovation were confirmed. Originality/value: This study is original, in that it represents a first effort in comparing perceptions of craft brewery operators across various countries. This comparison identifies ways in which craft brewery operators could maximise the potential of their firms. For example, the manifested interest in innovating through new craft beer recipes, or blending gastronomy and craft beer underlines alternative forms of adding value to craft brewing production. Importantly, some of these innovating practices differ based on participants' country; such differences could also be considered by craft brewery operators.